Studi Stabilitas Peralihan di Sistem Pembangkit Listrik Tenaga Disel Merawang - Asyari, Hasyim; Asmar; Sunanda, Wahri (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
The Merawang diesel power plant (PLTD) as one of the generating units in the Bangka area, the Bangka Belitung region, operates 9 generator units and 9 voltage step-up transformers. The output voltage will be supplied through the 150 kV SUTT. In this study, transient stability will be analyzed in the condition of 9 generators operating at PLTD Merawang. Transient analysis was performed using the Runge-Kutta method. When the 9 PLTD Merawang generators were operating, the fastest critical disconnection time was 0.11 seconds, which resulted in a 3-phase fault on the line at point D, the line at point E, and the line at point F.